Pengaruh Profitabilitas, Leverage, dan Risiko Perusahaan terhadap Penghindaran Pajak Sektor Basic Materials Periode 2020-2024 - Karina Christanti Victoria Sitorus; Dian Hakip Nurdiansyah; Rizke Wiliyanti (Pusat Riset dan Inovasi Nasional, 2026)
Low tax compliance in Indonesia reflects low tax morale and a lack of incentives for voluntary tax compliance. The purpose of this study is to examine the effect of profitability, leverage, and corporate risk on tax avoidance. The method used is a quantitative method using sec-ondary data obtained from the financial reports of basic material sector companies listed on the Indonesia Stock Exchange for the period 2020-2024. Based on purposive sampling, the total sample of this study was 38 observations, with the sample data analysis technique being multiple linear regression. This study concludes that profitability has no effect on tax avoidance, leverage has a positive effect on tax avoidance, and corporate risk has a negative effect on tax avoidance.